Analisis Kajian Sumber dan Nilai-Nilai Manajemen Pendidikan Islam - Ismatul Izzah (Mudir : Jurnal Manajemen Pendidikan, 2022)
The Islamic management system emphasizes that some of you are given by Allah to others in the skills, knowledge, expertise and temperament that are most important for smooth management. Emphasis on obedience and mutual respect, cooperation, equality of opportunity, commitment to work and full use of capacity. The purpose of this study is to find a combination or correlation of values contained in pure management science with Islamic education management. The key models of Islamic management are falah, aml pious, patient, fair, sincere, trustworthy and ihsan. This is the foundation on which the building of the Islamic management system is erected as a minaret. The management values of Islamic education which are sourced from the Qur'an, Hadith and Ijtihad of the ulama' are useful for developing human relations in the work environment, which does not allow anyone to exploit others as is usually done in other systems. The results of this study indicate that current management can be defined as the process of "Getting things done by someone else". Following this concept, as a Manager of an educational institution, one must be able to understand as a person working through other people. therefore, know not only what to do but also how to achieve it to achieve success. Sources of value from Islamic education management can be categorized as a combination of the Qur'an and hadith as well as elements of modern management.